Six-membered ring systems: with O and/or S atoms - Santos, Clementina M.M. (2013)
A large variety of publications have emerged in 2012 involving O- and S-6- membered ring systems. The increasing number of reviews and other communica- tions dedicated to natural and synthetic derivatives and their biological significance highlights the importance of these heterocycles. Reviews on natural products involve biosynthesis and isolation of enantiomeric derivatives h12AGE4802i, biosynthesis, isolation, synthesis, and biological studies on the pederin family h12NPR980i and xanthones obtained from fungi, lichens, and bacteria h12CR3717i and on the potential chemotherapeutic value of phyto- chemical products and plant extracts as antidiabetic h12NPR580i, antimicrobial, and resistance-modifying agents h12NPR1007i. A more specific review covers a structure–activity relationship of endoperoxides from marine origin and their antitry- panosomal activity h12OBC7197i. New synthetic routes to naturally occurring, biologically active pyran derivatives have been the object of several papers. Different approaches have been discussed for the total synthesis of tetrahydropyran-containing natural products (")-zampanolide h12CEJ16868, 12EJO4130, 12OL3408i, (")-aspergillides A and B h12H(85)587, 12H(85)1255, 12TA252i, (þ)-neopeltolide h12JOC2225, 12JOC9840, 12H(85) 1255i, or their macrolactone core h12OBC3689, 12OL2346i. The total synthesis of bistramide A h12CEJ7452i and (þ)-kalihinol A h12CC901i and the stereoselec- tive synthesis of a fragment of bryostatin h12S3077, 12TL6163i have also been sur- veyed. Other papers relate the total synthesis of naturally occurring carbocyclic and heterocyclic-fused pyran compounds, such as (")-dysiherbaine h12CC6295i, penos- tatin B h12OL244i, Greek tobacco lactonic products, and analogues h12TL4293i and on the structurally intriguing limonoids andhraxylocarpins A–E h12CEJ14342i. The stereocontrolled synthesis of fused tetrahydropyrans was used in the preparation of blepharocalyxin D h12AGE3901i. Polyphenolic heterocyclic compounds have also received great attention in 2012. The biological activities and the chemistry of prenylated caged xanthones h12PCB78i, the occurrence of sesquiterpene coumarins h12PR77i, and the medicinal properties of the xanthone mangiferin h12MRME412i have been reviewed. An overview on the asymmetric syntheses of flavanones and chromanones h12EJO449i, on the synthesis and reactivity of flavones h12T8523i and xanthones h12COC2818i, on the synthesis and biosynthesis of biocoumarins h12T2553i, and on the synthesis and applications of flavylium compounds h12CSR869i has been discussed. The most recent developments in the synthesis and applications of sultones, a very important class of sulfur compounds, were reported h12CR5339i. A review on xanthene-based fluorescent probes for sensing cations, anions, bio- logical species, and enzyme activity has described the spiro-ring-opening approach with a focus on the major mechanisms controlling their luminescence behavior h12CR1910i. The design and synthesis of other derivatives to be used as sensors of gold species h12CC11229i and other specific metal cations h12PC823i have also been described. Recent advances related to coumarin-derived fluorescent chemosen- sors for metal ions h12COC2690i and to monitoring in vitro analysis and cellular imaging of monoamine oxidase activity h12CC6833i have been discussed. The study of various organic chromophores allowed the synthesis of novel dica- tionic phloroglucinol-type bisflavylium pigments h12SL2053i, and the optical and spectroscopic properties of several synthetic 6-aryldibenzo[b,d]pyrylium salts were explored h12TL6433i. Discussion of specific reactions leading to O- and S-membered heterocyclic compounds covers intramolecular radical cyclization h12S2475i and asymmetric enamine and dienamine catalysis h12EJO865i, oxa-Michael h12CSR988i and dom- ino Knoevenagel–hetero-Diels–Alder (hDA) reactions h12T5693i, and the versatility in cycloadditions as well as nucleophilic reactions using o-quinones h12CSR1050i. The use of specific reagents relevant to this chapter includes molecular iodine h12CEJ5460, 12COS561i, samarium diiodide–water for selective reductive transfor- mations h12CC330i, o-quinone methides as versatile intermediates h12CEJ9160i, InCl3 as catalyst h12T8683i, and gold and platinum p-acid mediated insertion of alkynes into carbon–heteroatom s-bonds h12S3401i. The remainder of this chapter discusses the most studied transformations on O- and S-6-membered heterocycles.